The Main Drivers of the Raw Materials and ICT Sectors in Poland Using PESTEL Analysis - Patrycja Bąk; Marta Sukiennik; Barbara Kowal (Energies)
Poland is a country rich in mineral resources with a diversified resource base. Energy resources play a key role, as they are strategic resources ensuring the country’s energy security. Strategic resources, the recovery of which is highly risky and the possibilities of substitution are small, are critical resources for the Polish economy. These are the resources included in the list of critical resources for the European Union. The conducted review of mineral resources in Poland showed a large difference between the levels of actual resources and the resources of deposits. Therefore, supporting the mineral resources market is one of the key strategic areas of the Polish economy. This study aims to identify barriers that have a significant impact on the activities of entities in the raw materials sector. The tool used was the PESTEL analysis of companies operating in the raw materials sector. The aim of this study based on the assessment of experts familiar with the raw materials market and dealing with its challenges was to determine the main factors driving the raw materials market. These include the EU’s decarbonization policy, a complex system and relatively high level of taxes, a lack of qualified specialists, a market delay in terms of technological development, an environmental policy focused on a circular economy and renewables, and the problem of raw material depletion. The earlier identification of the market gap in the mineral resources industry in Poland in terms of business development opportunities indicated that IT and ICT would be possible directions of development. Therefore, an analysis of the industry was carried out in terms of business development opportunities. An assessment of the impact of individual factors on the activities of IT entities in the raw materials sector in Poland was carried out. The factors that most determine running a business in the diagnosed IT gap in the RM include a lack of government support for IT investments, new trends resulting from the growing importance of ICT in everyday life, the pandemic situation and the subsequent crisis of many companies on the market, the unstable financial condition of the main customer groups, and the lack of qualified personnel, equipment, and appropriate technology. The presented results may have practical implications, among others, for new economic players who want to establish their companies and conquer the raw materials market. On the one hand, they indicate opportunities, and on the other, they point to threats that may appear in their business life.